Abstrak Analisis Orientasi Pasar Dan Keunggulan Bersaing Dalam Melakukan Upaya Keberlangsungan UMKM Pada Masa Covid-19 (Survey Pada UMKM Minuman Di Kota Sukabumi) - Fitriani Fitriani; R Muhammad Danial; Kokom Komariah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The research was aimed at determining the amount of the influence of market orientation and competitive advantage toward sustainability caused by a decline in sales of beverage Small-Middle Enterprises (SMEs) in Sukabumi City. The objects of the research were Market Orientation (variable X1), Competitive Advantage (variable X2) and Sustainability (variable Y). The research methods applied was quantitative method with descriptive and associative approach, namely a method that deployed statistical calculations aimed to determine the influence or relationship of two or more variables. The techniques of analyzing data applied were commenced from validity test, reliability and normality tests, also supported by the Test-F, multiple correlation coefficient, determination coefficient, multiple linear regression and Test-T to determine the extent of the influence of the two independent variables studied on the dependent variable. Based on the results of the research, the relationship between market orientation and sustainability is amounted to -0.265 and the significant value is amounted to 0.793, indicating that there is a negative and insignificant influence. In addition to that, the competitive advantage is amounted to 14,412 and the significant value is amounted to 0.000 which means there is a positive and significant influence because t > 0. The influence of market orientation and competitive advantage toward sustainability is aggregated to 0.856 or namely 85.6%. Therefore, it can be observed that the influence of market orientation and competitive advantage toward sustainability has a strong influence. Thus, the one that has the biggest influence on sustainability is the competitive advantage variable. Keywords: Market Orientation, Competitive Advantage, Sustainability